Genetic diversity based on protein/isozyme analysis among populations of beef cattle (Bos indicus) from selected agroecological zones in the Philippines - Laude, Rita P.; Aquino, Genevieve B.; Tandang, Rosalina N.; Doydora, Marianito M.; Santos, Mary Ann J.; Austria, Joyce A.; Barile, Monique D.; Rodriguez, Jae Joseph Russell B.; Sevilla, Cesar C. (2006)
Protein/isozyme analysis using starch gel electrophoresis of 620 beef cattle plasma/serum samples was conducted to evaluate genetic diversity among populations from 20 selected agroecological zones in the Philippines [Ilocos, Pangasinan, Tarlac, Batangas (pooled with Cavite and Laguna populations), Romblon, Sorsogon, Siquijor, Cebu, Bohol, Negros, Guimaras, Oton, Tobias Fonier, San Remigio, Tibiao, Bukidnon, Camiguin, South Cotabato, Misamis Occidental, and Zamboanga]. Nine loci, namely, albumin (Alb), transferrin (Trf), esterases (Est1, Est2 and Est3), acid phosphatases (Acph1 and Acph2) and malate dehydrogenase (Mdh 1 and Mdh2) were studied. Except for albumin (Alb) with one genotype AA, all other loci were polymorphic. Six genotypes (AA, AB, AC, BB, BC and CC), were observed for Trf; three genotypes (AA, AB and BB), each for Est1, Est2 and Est3; six genotypes (AA, AB, AC, BB, BC and CC) each for Acph1 and Acph2, four genotypes (AA, AB, AC and BB) for Mdh1 and three genotypes (AA, AB and BB) for Mdh2. Intrapopulation genetic relationship based on the proportion of polymorphic loci and the average number of alleles was highest in Bohol and Negros and at 88.89% and 2.1111, respectively and lowest in Ilocos and Siquijor at 44.44% and 1.5556, respectively. The beef cattle populations of Tibiao and Tobias Fonier showed the highest degree of relatedness; hence, they shared the most common alleles as indicated by their low genetic distance of 0.0034. The genetically distant relationship between the populations of Siquijor and Cebu based on genetic distance value of 0.3357 and the two separate groups based on the dendrogram, Principal Component Analysis (PCA) and admixture correspond with the findings of Aquino (2004). Using microsatellite analysis, Aquino and her co-workers identified Siquijor cattle as Taurine type and Bohol cattle, a group closely related to Cebu cattle, as predominantly Bali type.
Keywords: Genetic polymorphisms; Beef cattle